Tuning the Transglycosylation Reaction of a GH11 Xylanase by a Delicate Enhancement of its Thumb Flexibility. (16th March 2021) - Marneth, Kim; van den Elst, Hans; Cramer‐Blok, Anneloes; Codee, Jeroen; Overkleeft, Hermen S.; Aerts, Johannes M. F. G.; Ubbink, Marcellus; Ben Bdira, Fredj
Abstract: Glycoside hydrolases (GHs) are attractive tools for multiple biotechnological applications. In conjunction with their hydrolytic function, GHs can perform transglycosylation under specific conditions. In nature, oligosaccharide synthesis is performed by glycosyltransferases (GTs); however, the industrial use of GTs is limited by their instability in solution. A key difference between GTs and GHs is the flexibility of their binding site architecture. We have used the xylanase from Bacillus circulans (BCX) to study the interplay between active‐site flexibility and transglycosylation. Residues of the BCX "thumb" were substituted to increase the flexibility of the enzyme binding site. Replacement of the highly conserved residue P116 with glycine shifted the balance of the BCX enzymatic reaction toward transglycosylation. The effects of this point mutation on the structure and dynamics of BCX were investigated by NMR spectroscopy. The P116G mutation induces subtle changes in the configuration of the thumb and enhances the millisecond dynamics of the active site. Based on our findings, we propose the remodelling of the GH enzymes glycon site flexibility as a strategy to improve the transglycosylation efficiency of these biotechnologically important catalysts. Abstract : Shifting the balance : Glycoside hydrolases are attractive tools for the enzymatic synthesis of carbohydrates. We used the xylanase from B. circulans (BCX) to study the interplay between active‐site flexibility and the transglycosylation reaction. A point mutation that enhances the flexibility and dynamics of BCX active site shifts the balance of the enzymatic reaction toward transglycosylation.